Comparison of Maternal and Perinatal Outcomes between Severe Preeclampsia without Complications and with HELLP Syndrome - Riva, Salma Nisrina; Pribadi, Adhi; Siddiq, Amillia (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2024)
Introduction: Maternal and perinatal outcomes in severe preeclampsia conditions, without or accompanied by HELLP syndrome, are variable. There is currently a lack of research data in Indonesia comparing maternal and perinatal outcomes in both conditions. This study compares pregnancy outcomes between severe preeclampsia with no complications and severe preeclampsia with HELLP syndrome.Methods: This study employs an observational analytical approach, utilizing a retrospective cross-sectional design. The samplings contain 92 patients from the medical records of patients who were diagnosed with preeclampsia without complications and severe preeclampsia with HELLP syndrome at Hasan Sadikin Hospital Bandung from January 2021 to December 2023.Results: It was found that maternal with HELLP syndrome are five times more at risk for eclampsia compared to maternal with preeclampsia without complications. Maternal who have severe preeclampsia accompanied by HELLP are two times more at risk of having labor under 34 weeks or preterm compared to maternal with preeclampsia without complications. Other outcomes, including maternal mortality, DIC, acute renal failure, pulmonary edema, antepartum hemorrhage, as well as perinatal mortality, FGR, IUFD, and perinatal asphyxia, did not show a statistically significant difference in proportion (p > 0.05).Conclusion: There is a relationship between maternal and perinatal outcomes in severe preeclampsia without complications or with HELLP syndrome.Perbandingan Luaran Maternal dan Perinatal antara Preeklamsia Berat Tanpa Penyulit dan dengan Sindrom HELLPAbstrakPendahuluan: Luaran maternal dan perinatal pada kondisi preeklamsia berat, tanpa dan dengan sindrom HELLP, tergolong bervariasi. Saat ini masih minim data penelitian di Indonesia yang membandingkan hasil luaran maternal dan perinatal pada kedua kondisi tersebut. Penelitian ini bertujuan untuk mengetahui perbandingan luaran kehamilan antara preeklamsia berat tanpa komplikasi dan preeklamsia berat dengan Sindrom HELLP. Metode: Metode yang digunakan dalam penelitian ini adalah analitik observasional dengan desain potong lintang retrospektif. Sampel penelitian ini adalah 92 pasien dari rekam medis pasien yang didiagnosis preeklamsia tanpa komplikasi dan preeklamsia berat dengan Sindrom HELLP di Rumah Sakit Hasan Sadikin Bandung pada periode Januari 2021 hingga Desember 2023.Hasil: Hasil penelitian menunjukkan bahwa ibu dengan sindrom HELLP berisiko lima kali lebih besar untuk mengalami eklampsia dibandingkan dengan ibu dengan preeklampsia tanpa komplikasi. Ibu yang mengalami preeklampsia berat disertai HELLP berisiko dua kali lebih besar untuk mengalami persalinan di bawah 34 minggu atau prematur dibandingkan dengan ibu yang mengalami preeklampsia tanpa komplikasi. Luaran lain seperti kematian ibu, DIC, gagal ginjal akut, edema paru, perdarahan antepartum dan juga kematian perinatal, FGR, IUFD, asfiksia perinatal tidak ada perbedaan proporsi yang bermakna secara statistik (p>0,05).Kesimpulan: Terdapat hubungan luaran maternal dan perinatal antara preeklamsia berat tanpa komplikasi atau dengan sindrom HELLP.Kata kunci: Luaran Maternal, Perinatal, Sindrom HELLP